THE EFFECT OF VERTICAL, HORIZONTAL AND DIAGONAL COMMUNICATIONS ON EMPLOYEE PERFORMANCE AT THE TRAINING BOARDMALUKU PROVINCE - Rido Latuheru (JURNAL BADATI, 2022)
This study aims to analyze (1) the effect of communication consisting of vertical, horizontal and diagonal communication on performance and (2) the most dominant variable affecting employee performance at the Education and Training Agency of Maluku Province. The number of samples is determined based on the Kresjie table, where if the population is 231 people, at an error rate of 10%, the number of samples is 125 people, which is determined by simple random sampling. Data were analyzed by multiple linear regression. The results showed that (1) vertical, horizontal and diagonal communication together had a positive and significant effect on the performance of the Education and Training Agency employees of Maluku Province by 78.9% and (2) horizontal communication was the most dominant variable affecting the performance of the Education and Training Agency employees. Maluku Province is 64.9%.